What is behind stagnant unemployment in Ukraine: the role of the informal sector - Olga Kupets (Institute for the Study of Labor (IZA), 2005)
In recent years there has been much policy discussion of the impact of unemployment benefits and other factors on unemployment duration in developed and transition countries. This paper presents first evidence on the determinants of unemployment duration in Ukraine. Using individual-level data from the first wave of the Ukrainian Longitudinal Monitoring Survey (ULMS -2003), which cover the period 1997-2003, we find no significant effect of benefit receipt on exits from unemployment. However, our survival analysis confirms the hypothesis that income from casual activities or subsidiary farming has strong disincentive effect on the hazard of re-employment in Ukraine. The results also indicate that individual's age, marital status and gender, the level of education and place of residence are significantly related to the total time spent out of work. The estimates of the baseline hazard parameters do not suggest any marked negative duration dependence.
Keywords: J64; J68; P23; 330; unemployment duration; casual work; transition countries; semiparametric duration analysis